Analisis Pengaruh Kantor, ATM dan Imbal Hasil terhadap Dana Pihak Ketiga Bank Syariah di Indonesia - Gagat Panggah Mulyo; Nurwahidin Nurwahidin (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Signal Theory conveys that financial reports are very important tools for stakeholders. In the banking industry, especially Islamic Banks (BUS) are the main benchmark in increasing the Islamic banking market. This success appeared in the form of a signal in the form of a continuous increase in the position of Third Party Funds (DPK) over time. This study aims to analyze the effect of the number of offices, the number of ATM machines and the rate of return on DPK BUS in Indonesia. The methodology used is multiple linear regression analysis. The result of the analysis is that BRANCH (number of offices) has a negative but not significant effect on FUND (DPK), while ATM (ATM machines) has a significant positive effect on FUND and RETURN (yield rate) has a significant negative effect on FUND. The simultaneous test results, namely BRANCH, ATM and RETURN simultaneously affect FUND